Factors Associated with Family Planning Participation among Mothers of Toddlers in Lamongan - Kurniasari, Sinta (Universitas Muhammadiyah Lamongan, 2022)
Introduction: The use of contraception when a child is under five must be considered because mother need to regulate the spacing of their children and provide more optimal care for their toddlers. Based on the 2019 Family Data update, the use of contraception amongmothers with toddlers in Moro Village is still low. This study was conducted to determine the factors associated with the participation of a mother’s toddler in family planning.Methods: The study used quantitative methods with non- probability sampling. The research sample was drawn by total sampling, namely all couples of childbearing age who had toddlers and were recorded in the 2021 Family Data Collection, as many as 42 people. The study's independent variables were age, education level, number of children, and BKB (Bina Keluarga Balita) activities. Meanwhile, the dependent variable of the research is family planning participation. Data were collected through secondary data from the 2021 Family Data Collection Form. Data analysis used the Chi-Square test with a significance level of 5%.Results: The statistical tests showed a significant relationship between education level (p=0.035) and BKB activity (p=0.026) with family planning participation. However, there was no significant relationship between age (p=0.921) and some children (p=0.912) with family planning participation for mothers under five in Moro Village.Conclusion: There is a relationship between the level of education and BKB activity with family planning participation. Therefore, there is a need for family planning counselling and the use of BKB in socializing the use of contraception for women with toddlers.